Synthesis of Nanoparticles Powder from Seeds Extract Clove by Ionic Gelation process - D. Hussein, Amel (University of Thi-Qar Journal, 2024)
In this work, a nanopowder of seed extract clove was prepared in a simple loaded ionic gelation method using several enhancements to prevent particle aggregation as a surfactant to chitosan solutions [Tween 80: 0.5% (v/v)]. The clove seed extract was loaded on polymeric chitosan under a vortex until complete added the quantity. Chitosan Tripolyphosphate (TPP) solution in the ratio (2:1v/v) at room temperature under magnetic stirring was added dropwise using a syringe. The result was characterized by FTIR, SEM, and TEM almost nanorod in shape and the range of size 50 nm-1?m. It is used in agricultural products, biomedical, cosmetics, improving the hardness of dental fillings, a natural analgesic, antibiotic, etc.